Composite Materials Based on Shape‐Memory Ti2NiCu Alloy for Frontier Micro‐ and Nanomechanical Applications. Issue 8 (3rd July 2017) - Lega, Peter; Koledov, Victor; Orlov, Andrey; Kuchin, Dmitry; Frolov, Aleksey; Shavrov, Vladimir; Martynova, Alexandra; Irzhak, Artemii; Shelyakov, Alexander; Sampath, V.; Khovaylo, Vladimir; Ari‐Gur, Pnina
Abstract : Composite materials based on Ti2 NiCu alloy, exhibiting shape memory effect (SME), have the unique capability of temperature‐controlled reversible actuation on micro‐ and nanoscale. Three approaches to realizing this objective are demonstrated. The first one involves creating an amorphous‐crystalline composite by passing accurately controlled electrical pulses through a rapidly‐quenched amorphous Ti2 NiCu ribbon. After undergoing partial crystallization (40–60% of crystalline phase), the composite acquires SME, and can be trained to undergo reversible deformations by a single bend in the martensitic condition. The second approach involves a layered composite consisting of a layer of Ti2 NiCu and an elastic metallic layer, such as Pt. It is found that the reversible deformation of the Ti2 NiCu/Pt composite created by FIB milling is >1%, when the thickness of SME layer is reduced from 1 μm to 100 nm. Further reduction (below 100 nm) results in smaller deformation. The third approach combines these two methods. A layer of crystalline Ti2 NiCu is covered by a layer of the same alloy in the amorphous state using FIB. The authors believe that these composites, exhibiting SME, will trigger the fabrication of many novel devices and open up new opportunities in diverse areas of nanoscience and nanotechnology. Abstract : This manuscript presents three approaches to realizing composite materials based on Ti2NiCu alloy, exhibiting shape memory effect for temperature‐controlled reversible actuation on micro‐ and nanoscale. The authors believe that these composites will open up new opportunities in diverse areas of nanoscience and nanotechnology.